Role of long-term memory in object-based attention for the maintenance of binding in visual working memory - Sun, Nana; Han, Han; Lyu, Peijin; Song, Ruijun (Frontiers in Psychology, 2025)
BackgroundPast research has suggested that binding retention requires more object-based attention than feature retention in visual working memory (VWM). Long-term memory (LTM) is also believed to contribute to VWM.ObjectivesWe investigated whether LTM reduces the object-based attention required to maintain bindings.MethodsParticipants were familiarized with specific items prior to the VWM task to establish LTM representations, and we included a Duncan task in the maintenance phase of the VWM task to consume object-based attention.ResultsResults revealed that consuming object-based attention disproportionately impaired bindings compared to features for unfamiliar objects but not for familiar ones (Experiment 1). This effect could not be attributed to differences in memory set sizes between the familiar-objects condition and the unfamiliar-objects condition (Experiment 2) or to differences among participants between the two levels of the LTM condition (Experiment 3).ConclusionThese findings demonstrate that LTM availability modulates the role of object-based attention in retaining bindings in VWM, with bindings requiring more object-based attention than individual features for unfamiliar objects but not for familiar objects.